The Effect of Storage Time of Fortified Goat Milk Yoghurt White Rice Bran Flour on Organoleptic Physical Characteristics, pH Value, Amount of Coliform and Salmonella sp. Contamination - Haskito, Ajeng Erika Prihatuti; Mahdi, Chanif; Almara, Faniar Tasha; Bina, Restu Wika (Universitas Airlangga, 2023)
This study aimed to determine the effect of storage time for fortified goat's milk yogurt white rice bran flour on organoleptic physical characteristics, pH value, amount of coliform and Salmonella sp. contamination. A total of 20 samples were divided into five treatment groups, based on storage time of 0, 1, 2, 3, 4 weeks, and 4 replications. Every week, tests for organoleptic physical characteristics were carried out using 20 semi-trained panelists, measuring pH values using a pH meter, evaluating the amount of coliform contamination using the MPN method, and Salmonella sp. using SSA media, Gram stain, and TSIA media. Data of organoleptic physical characteristics was analyzed using Kruskal-Wallis followed by Mann-Whitney, data on the amount of coliform contamination and pH values were analyzed using OneWay ANOVA followed by Tukey. Qualitative data on contamination of Salmonella sp. descriptively. The results showed that storage time had a significant effect (p<0,05) on organoleptic physical characteristics, appearance, taste and aroma criteria, but had no significant effect (p>0,05) on color criteria. The results on the amount of coliform contamination and the pH value showed a significant difference (p<0,05). Results on contamination of Salmonella sp. no effect on storage time. In conclusion, a maximum shelf life of two weeks can still be recommended for consumption.